Advances in Stem Cell and Regenerative Therapies in Autoimmune and Metabolic Diseases: Implications for Healthy Longevity - Lakey, Jonathan R. T.; Alexander, Michael; Chan, Mike K. S.; Nalapko, Yuriy; Wong, Michelle B. F.; Cox, Desiree C. T. (International Journal of Translational Science, 2024)
Type 1 diabetes (T1D) is an important autoimmune disease characterized by the destruction of insulin-secreting β-cells in pancreatic islets of Langerhans resulting in hyperglycemia. More than 1.3 people in United States are suffering from T1D, and current treatments have failed to offer a lasting cure. T1D management requires lifelong daily injections of exogenous insulin to control blood sugar levels and secondary complications of this progressive disease, unless receiving pancreas or islet transplant with its associated risks from immunosuppression. Peptide therapy aims to alter the response of cells by inducing or reducing cellular responses appropriate to the type of peptides used. The aim of this study was to investigate the protective effect on autoimmunity of Mito Organelle (MO) Peptides on the function and survival of peptides on pancreatic β-cells in non-obese diabetes (NOD) mice model. MO peptide product (Biopep Inc) is a mixture of organ-specific cellular extracts that were extracted from organ specific cells, homogenized, filtered, and sterilized. MO Peptides administered twice-weekly (IM) over 17-week period in NOD mice model were able to prevent the progression of autoimmune-mediated β–cell destruction and the onset of hyperglycemia (blood glucose >300 mg dL) as compared to the saline treated control mice. These studies will help understand the mechanisms of immunological protection in T1D and may serve as a model for other autoimmune disorders with peptides.